F: Manajemen Strategi Pencegahan Dan Penurunan Stunting - Deysi Swandayani; Rajindra Rajindra; Abdul Kadri (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
The prevalence of stunting in Central Sulawesi is 27.2%, still above the national average of 24.2%, with Sigi Regency as one of the highest areas (24.6%). In Dolo District, the prevalence reached 22.34% (218 out of 976 toddlers) in 2024, with priority loci in Wisolo, Poi, and Waturalele Villages. Low maternal knowledge, inappropriate parenting patterns, and poor sanitation are the main obstacles in achieving the target of a 14.2% reduction by 2029. This study aims to analyze the causes of stunting and develop improvement strategies through a SWOT analysis. The qualitative research method with a strategic management approach (environmental observation, formulation, implementation, and evaluation) uses IFE, EFE, IE, and SWOT matrix analysis. Informants included the head of the Community Health Center, stunting program managers, village midwives, and the Stunting Reduction Acceleration Team. Data analysis involved environmental observation, formulation, implementation, and evaluation using the IFE, EFE, and IE matrix instruments, as well as a SWOT analysis. The analysis identified key contributing factors, including a lack of nutritional knowledge, parenting practices, and access to sanitation. Strategies implemented included the One Million Eggs program, Tanggang Shining, and specific and sensitive nutrition interventions. The SWOT analysis mapped the organization's position to formulate data-driven improvement strategies to optimize existing resources by strengthening convergence between 14 Regional Apparatus Organizations (OPDs) and utilizing real-world data to address field coordination challenges, ensuring the achievement of the stunting reduction target. Optimizing strategic management through cross-sectoral program integration and strengthening public education is key to accelerating stunting reduction.Keywords: Strategic Management; Stunting; SWOT Analysis.